Differential expression and modulation of EBI2 and 7α,25-OHC synthesizing (CH25H, CYP7B1) and degrading (HSD3B7) enzymes in mouse and human brain vascular cells. - Fionä Caratis; Bartosz Karaszewski; Ilona Klejbor; Tomomi Furihata; Aleksandra Rutkowska (PLoS ONE, 2025)
The endogenous ligand for the EBI2 receptor, oxysterol 7α,25OHC, crucial for immune responses, is finely regulated by CH25H, CYP7B1 and HSD3B7 enzymes. Lymphoid stromal cells and follicular dendritic cells within T cell follicles maintain a gradient of 7α,25OHC, with stromal cells increasing and dendritic cells decreasing its concentration. This gradient is pivotal for proper B cell positioning in lymphoid tissue. In the animal model of multiple sclerosis, the experimental autoimmune encephalomyelitis, the levels of 7α,25OHC rapidly increase in the central nervous system driving the migration of EBI2 expressing immune cells through the blood-brain barrier (BBB). To explore if blood vessel cells in the brain express these enzymes, we examined normal mouse brain microvessels and studied changes in their expression during inflammation. Ebi2 was abundantly expressed in endothelial cells, pericytes/smooth muscle cells, and astrocytic endfeet. Ch25h, Cyp7b1, and Hsd3b7 were variably detected in each cell type, suggesting their active involvement in oxysterol 7α,25OHC synthesis and gradient maintenance under normal conditions. Significant species-specific differences emerged in EBI2 and the enzyme levels between mouse and human BBB-forming cells. Under acute inflammatory conditions, Ebi2 and synthesizing enzyme modulation occurred in the brain, with the magnitude and direction of change based on the enzyme. Lastly, in an in vitro astrocyte migration model, CYP7B1 inhibitor clotrimazole, as well as EBI2 antagonist, NIBR189, inhibited lipopolysaccharide-induced cell migration indicating the involvement of EBI2 and its ligand in brain cell migration under inflammatory conditions.